Memória discursiva da ditadura no século XXI: visibilidades e opacidades democráticas - Sá, Israel de (2015)
In this study, we start from the observation that, in distinct positions, different memories about the dictatorial times are brought back to present times. On the one hand, the slow unfoldment of official documents from the Brazilian dictatorial times and the refusal to revise the Amnesty Law – established in 1979, during the process of political opening initiated by the regime – and, on the other hand, a large amount of material produced by the media about the period or related to its themes build a discursive confrontation that introduces the production (by the media) of a memory inserted between the democratic (the possibility of “saying everything”, and the debate on the official level) and the silence (saying it on the margins). Yet, the revision process of the Amnesty Law, in 2010, and the implementation of the National Truth Commission, by the Federal Government, in 2012, serve as the base events to create the possibility of commenting, analyzing and rewriting history, in addition to the production of this/these memory/memories. Based on the theoretical propositions of the French approach of Discourse Analysis, in line with studies on the memory of different fields of the human and social sciences, we analyze in this study three types of materials: a) texts that were produced in the dictatorial period, especially by the independent media, that are constantly reproduced, republished and currently published (such as the magazine Pif Paf and the newspapers O Pasquim and Ex-); b) special editions of the magazines and newspapers published in the XXI century, besides documentaries and films that deal with facts relating to that period; c) texts produced by the media resulting from the revision process of the Amnesty Law and the establishment of the National Truth Commission. With that, we seek to understand the role of memory to the production and (re)construction of the history of the period in which Brazil was under military dictatorship, and the deepening of the democratic society. As a result, we understand that memories of the Brazilian military dictatorship are formed from a reordering, between opacity and visibility, of the ways of saying; in these 30 post-dictatorship years new discursive regimes emerged, enabling „to say the dictatorship‟, which sets, in Brazil, a will of memory and a step towards the consolidation of its democracy.